Pemanfaatan Barang Jaminan Hutang Benda Bergerak Tanpa Kesepakatan Bersama Menurut Imam Syafi’i: Studi Kasus Kecamatan Medan Deli, Kelurahan Tanjung Mulia Hilir, Kota Medan - Aida Yunita; Tetty Marlina Tarigan (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The use of pawn guarantees in Shafi'i's view is strictly prohibited because it is easily exposed to the potential of riba fadhilah in it. However, what happened in Tanjung Mulia Hilir Village was not the case, this is because the pawn owner used the item even to make a profit. This journal discusses how the rules for the implementation and utilization of pawns according to Imam Syafi'i, the practice of implementing pawns in Tanjung Mulia Hilir Village and the analysis of the illegality of using pawn goods used as collateral according to Imam Shafi'i. The research method in this journal uses empirical research methods and also by using interviews as research instruments. The results of the study proved that the implementation and utilization of pawn collateral according to Imam Shafi'i was not allowed even though it was located and there was an agreement between the two parties.